(untitled) (ETIMA, 2024)
This paper discusses SCADA systems, their planning and projecting, and their increasing implementation in industry. SCADA are used for 24-hour supervision and management in systems and processes. Industry requires daily supervision and management of processes, and technology advancements enable more efficient and creative management. SCADA systems enable control and supervision of complex systems, and also enabling employees to be more creative and productive. SCADA systems enable the management of subsystems in different locations, enhancing overall efficiency and productivity.